In memoriam - CPH 54(1) (Czasopismo Prawno-Historyczne, 2002)
Karol Rebro, 1912-2000 (Józef Ciągwa) … 483 Jörg K. Hoensch, 1935-2001 (Henryk Olszewski) ... 485 Tomasz Opas, 1923-2001 (Władysław Ćwiek) ... 489 Irena Dwornicka, 1953-2002 (Stanisław Grodziski) ... 493